UPAYA MENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN KELAS 3 DENGAN PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE MAKE A MATCH BERBANTUAN MEDIA KARTU PINTAR DI SDN BUDURAN 02 - Meilinda Dyah Adistiya; Eka Putri. A. B; Hanifa Septia Nur Aini; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the mathematics learning outcomes of third-grade students in semester II of SDN Buduran 02 in the 2024/2025 academic year by implementing the cooperative model type make a match assisted by smart card media. This research is a classroom action research. The subjects of this study were all third-grade students of SDN Buduran 02 totaling 10 students with 5 male students and 5 female students. The object of the research conducted was the achievement of students' mathematics learning. Learning achievement data is presented using the learning achievement test method which is then analyzed descriptively. The indicator of success in this study is that student learning outcomes reach ≥ 70 with learning completeness ≥ 85%. The results of the study showed that in cycle 1 the average value of mathematics learning outcomes was 74 with classical completeness of 60% and in cycle II the average value of mathematics learning outcomes was 92 with classical success of 90%. Based on the results of this study, it shows that the application of the cooperative learning model type make a match assisted by smart card media on fraction material can improve the learning outcomes of grade 3 students of SDN Buduran 02 semester II of the 2024/2025 academic year.